AMIRY’S RHYME SKILL - Abdurakhmonova Olmoskhan Ilkhomjon kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article provides information about the rhyming poem system used in oriental classical literature. Information is given about the poet Amiriy, who created in the Kokand literary environment, and his skill in using rhyme.